2020
DOI: 10.1097/qai.0000000000002230
|View full text |Cite
|
Sign up to set email alerts
|

Network-Level Correlates of Sexual Risk Among Male Sex Workers in the United States: A Dyadic Analysis

Abstract: Background: Male sex workers (MSWs) are at increased risk of HIV infection in the United States. Research is limited on sexual and drug use network characteristics of MSWs. Setting: Community-based organization and health center in 2 US Northeast cities. Methods: One hundred MSWs completed a behavioral assessment and sexual and drug network inventory. Using dyadic analyses, we assessed whether network charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…2,5,14 Furthermore, research has suggested that women who experience greater economic instability may be more vulnerable to victimization within transactional sex relationships, 15,16 while drug use may increase the likelihood of engaging in higherrisk transactional sex. 17,18 Though this underscores the importance of examining the intersection of gender, poverty, culture, and other structural inequalities in the study of substance use and transactional sex, 8,[19][20][21] there remain gaps in the literature, including a limited understanding of transactional sex among populations who are from structurally disadvantaged rural communities-particularly among women, who are more likely to experience poverty and other vulnerabilities given traditional gender role expectations. 22 Considering recent concerns regarding a potential HIV outbreak in rural Appalachia, 23 coupled with a recent finding that rural females who inject drugs were nearly 4 times more likely than their male counterparts to report having recently engaged in transactional sex, 24 further examination of transactional sex among rural women who may be at higher risk is warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,14 Furthermore, research has suggested that women who experience greater economic instability may be more vulnerable to victimization within transactional sex relationships, 15,16 while drug use may increase the likelihood of engaging in higherrisk transactional sex. 17,18 Though this underscores the importance of examining the intersection of gender, poverty, culture, and other structural inequalities in the study of substance use and transactional sex, 8,[19][20][21] there remain gaps in the literature, including a limited understanding of transactional sex among populations who are from structurally disadvantaged rural communities-particularly among women, who are more likely to experience poverty and other vulnerabilities given traditional gender role expectations. 22 Considering recent concerns regarding a potential HIV outbreak in rural Appalachia, 23 coupled with a recent finding that rural females who inject drugs were nearly 4 times more likely than their male counterparts to report having recently engaged in transactional sex, 24 further examination of transactional sex among rural women who may be at higher risk is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…), increase the likelihood of engaging in transactional sex 2,5,14 . Furthermore, research has suggested that women who experience greater economic instability may be more vulnerable to victimization within transactional sex relationships, 15,16 while drug use may increase the likelihood of engaging in higher‐risk transactional sex 17,18 . Though this underscores the importance of examining the intersection of gender, poverty, culture, and other structural inequalities in the study of substance use and transactional sex, 8,19–21 there remain gaps in the literature, including a limited understanding of transactional sex among populations who are from structurally disadvantaged rural communities—particularly among women, who are more likely to experience poverty and other vulnerabilities given traditional gender role expectations 22…”
Section: Introductionmentioning
confidence: 99%
“…Among the contextual factors driving this behaviour, one of the most frequent reported was the use of recreational drugs with clients. [60][61][62] Drug use has been described as a social aspect of this type of work 63 which makes difficult to avoid with clients who are regular drug users, 61 and they are also used to improve sexual performance. 64 About the latter, recreational drugs initiate sexual interaction, 52,65-67 causing sexual arousal that facilitates sexual acts.…”
Section: Discussionmentioning
confidence: 99%
“…One of main factors was the use of recreational drugs with clients. [48][49][50] Authors describe the use of drugs with clients as a social aspect of their occupation, 51 while improving their performance. 52 Further, some argue that this is a difficult aspect to avoid with clients who are regular drug users.…”
Section: Discussionmentioning
confidence: 99%